Factors Influenced of Nurse Performance: The Mediating Role of Organization Commitment with SEM - PLS Approach - Supriyantoro; Rina Anindita; Retno Andrianti (Alta Dharma Publisher, 2022)
Introduction: COVID-19 positive cases in Jakarta continue to increase from day today. Objective: The study is aimed to examine and develop the variables which affect the performance of nurses who treat COVID-19 patients at the Islamic Hospital of Jakarta Sukapura. The hospital itself was assigned as a referral hospital for Covid-19 patients on an emergency basis. This assignment later created unrest from workers or medical personnel who worked at the hospitals, especially those who worked as nurses. Method: The research design used here is a descriptive quantitative approach using five main variables: Self - Efficacy; Job Stress, Organizational Commitment, and Nurse Performance, while the research instrument used a questionnaire with a Likert scale and distributed for 10 days. The sample used in this study used a total sampling technique comprised of 120 respondents, while the data analysis in this study used the SEM method assisted by the Smart PLS 3.2 program. Results: showed that self-efficacy had a positive and significant effect on organizational commitment and nurse performance. In addition, work stress has a negative impact on organizational commitment and does not affect nurse performance. The result of research also discovered that organizational commitment has a negative effect on the performance of nurses. Recommendation: results of this study can also be considered by the leadership at the Islamic Hospital of Jakarta Sukapura, DKI Jakarta, to improve the performance of its nurses